The Problematic of Economic Inequality in Criminal Cases of Theft Criminality in Medan City (Study Decision 974/Pid.B/2022/PN Mdn) - Suwarto, Suwarto (Lafadz Jaya Publisher, 2024)
The crime of theft is in Article 362 of the Criminal Code (KUHP) which states that anyone who takes an item, which wholly/partially belongs to another person, with the intention of possessing the item unlawfully, shall be punished for stealing with imprisonment for a lifetime. five years or a fine of up to nine thousand rupiah, but in fact there are many incidents of criminal acts in society, including cases of thieves in Decision Study 974/Pid.B/2022/PN Mdn). Crime cases in the city of Medan require exploratory handling to be minimized. Several factors that cause high crime rates include poverty, unemployment, lack of education, and low quality of life in society. Crime prevention in the city of Medan can be done through various efforts, including improving community welfare through economic empowerment programs, creating jobs, increasing access to education, and promoting rehabilitation and reintegration programs for former prisoners. Apart from that, strengthening the security system and law enforcement also needs to be done to reduce the rate of crime in this province. With comprehensive prevention efforts, it is hoped that criminal cases in the city of Medan can be reduced, and the community can live in a safe and peaceful environment.